Remo celebration in Blater community: traditional ritual communication in Madura cultural transformation - Julijanti, Dinara Maya; Suryandaru, Yayan Sakti; Artaria, Myrtati Dyah (Faculty of Communications Science, Dr. Soetomo University, 2020)
This study aimed to find the purpose of communication ritual within Remo of the Blater community in Madura, which helped to maintain traditions in the Madurese society. Remo celebration has existed in Madura for generations, since the Dutch colonisation era until now. This research employed the descriptive qualitative method. The informant of this research was the Blater communities in Bangkalan and Sampang districts as Remo performers. The methods of analysis were observations, in-depth interviews, and primary data collected from field research. We concluded that Remo in Madura, especially in Bangkalan Regency, still exists despite the rapid influence of global culture and information technology. Remo as a celebration tradition in Bangkalan Regency is a face-to-face ritual communication with symbolic power and as well as a ritual media for the Blater community in Madura. Remo celebration exists as a traditional medium of ritual communication to build a good relationship in the Madurese Blater community. In terms of local cultural values, Remo has a positive impact that contributes to the existence of the local tradition of Madura.